2022
DOI: 10.3390/f13070976
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Soil Surface Changes after Traffic of Various Wheeled Skidders with Close-Range Photogrammetry

Abstract: Soil surface is directly affected by heavy traffic of machinery during harvesting operations. Machine traffic often causes damage to forest soil which is visible on the surface (ruts) and invisible changes in, for example, bulk density, penetration resistance, etc. Close-range photogrammetry is the state-of-the-art method used for recording and evaluation of visible changes. This study aims to analyze soil surface changes caused by traffic of three types of wheeled skidders without a load on Cambisol soil in C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
3
1
Order By: Relevance
“…When comparing the calculated outcomes to those of previous research, it was found that Salmivaara et al 37 achieved a root RMSE of 0.035 m when employing a Light Detection and Ranging (LiDAR) sensor to measure the depth of wheel tracks. In their investigation of soil surface changes using close-range photogrammetry, Ferencík et al 26 found a range of RMSE between 0.026 m and 0.050 m. The RMSE values calculated for this investigation's row and column coordinates were smaller than the reported values.…”
Section: Resultscontrasting
confidence: 60%
See 1 more Smart Citation
“…When comparing the calculated outcomes to those of previous research, it was found that Salmivaara et al 37 achieved a root RMSE of 0.035 m when employing a Light Detection and Ranging (LiDAR) sensor to measure the depth of wheel tracks. In their investigation of soil surface changes using close-range photogrammetry, Ferencík et al 26 found a range of RMSE between 0.026 m and 0.050 m. The RMSE values calculated for this investigation's row and column coordinates were smaller than the reported values.…”
Section: Resultscontrasting
confidence: 60%
“…Liu et al 29 optimized the asphalt mix design using rut depth prediction for asphalt pavement. In their study, Ferenčík et al 26 utilized Close-range photogrammetry to quantify the depth of the rut formed by wheeled skidders within the University Forest Enterprise of the Technical University located in central Slovakia. The study by Zheng et al 30 examined the impact of rut in asphalt surfaces on the steering stability of autonomous vehicles.…”
Section: Introductionmentioning
confidence: 99%
“…In the recent literature, two other precision forestry approaches for the monitoring of soil disturbances after ground-based forest operations can be found; these are Structure-from-Motion (SfM) Photogrammetry and LiDAR [82,83]. Photogrammetry consists of a technique in which measurements made from one or more images are used to estimate the three-dimensional coordinates of points on a surface.…”
Section: Monitoring Environmental Sustainability Of Forest Operationsmentioning
confidence: 99%
“…Salmivaara et al [31] investigated the applicability of the 2D LiDAR system when measuring ruts and determined that the average error of this system is 3.5 cm. Water in the ruts makes it difficult to use photogrammetric methods and LiDAR technology and is a prominent problem in the studies mentioned and others [32][33][34]. Depending on the water depth, the error can be up to 15 cm [28].…”
Section: Introductionmentioning
confidence: 99%